Cellular RNA homologous to the Abelson murine leukemia virus transforming gene: expression and relationship to the viral sequence. - Wang, J Y (1983)
To examine the expression of the cellular homolog of the Abelson murine leukemia virus transforming gene (the v-abl sequence), a DNA probe representing the v-abl sequence was prepared. The probe detected two cytoplasmic polyadenylic acid-containing c-abl RNAs of about 6.5 and 5.5 kilobases in a variety of rodent cells, and slightly larger RNAs were detected in human cells. These two RNA species were found in all normal tissues or cell lines examined, but at differing concentrations: liver cells had the least, fibroblastic cell lines had the most. By using a probe able to detect the cellular but not the viral gene, the two RNAs were shown to be present in Abelson murine leukemia virus-transformed cells at levels found either in their untransformed counterparts or in similar cell types transformed by other means. The target cells of the virus have a somewhat elevated level of the two RNAs although expression of the c-abl gene is not restricted to these cells. The v-abl sequence lacks 0.35 and 0.85 kilobases of the c-abl RNA on the 5' and 3' ends, respectively. Thus, the Abelson murine leukemia virus transforming gene is an internal fragment of the transcript of a normal cellular gene.